Organização do trabalho e transtornos mentais comuns nos técnicos de enfermagem de um hospital público universitário de grande porte - Leão, Laysa de Oliveira Souza (2018)
Common Mental Disorder is an important public health problem today. It is a term used to name stress symptoms in the health worker (GOLDBERG; HUXLEY, 1993). Such symptoms may affect the professionals´ performance, causing absenteeism and job dissatisfaction. Among the professionals who are most likely to develop mental disorders, we can mention the nursing technicians, since they are in direct contact with the patients, work in unhealthy environments, there is a scarce number of professionals, inadequate compensation, double working hours, work under pressure for taking care of lives and face the devaluation of the profession. The objective of this research was to verify the relationship between Common Mental Disorder and the work organization of the nursing technicians of the surgical clinics of a University Hospital in Minas Gerais. The scenario was the surgical clinics of the HC / UFU, the sample was the nursing technicians and the data were collected from a structured questionnaire, validated by Mari and Williams (1986). Data analysis was performed using Office Excel® software and data processing and tabulation were performed by SPSS version 20. The study population consisted of 83 nursing technicians. The results showed a rate of 48.2% for the presence of Common Mental Disorder, with a predominance of females with 80%, with an age range between 41-50 years and graduated in a college or university. The greatest number of Common Mental Disorders was found in single, widowed or divorced people, with 52.5% having children and earning something between 3 and 4 minimum wages. Regarding the sector of performance, surgical clinics 1 and 2 obtained the greatest quantity of Common Mental Disorders, being 52.5% and 35%, respectively. Surgical 5 did not obtain any positive results for Common Mental Disorder. Statistical analysis indicated the labor sector, gender and the bigger number of children as the statistically significant variables for Common Mental Disorder (P = 0.007, P = 0.083, P = 0.084, respectively). The data referring to the sector of action indicates a strong inequality in the labor relations among surgical clinics, considering that they are employees of the same category, who receive the same salary for the work performed and who have the same contractual relationship. There is a need to review the planning of surgical clinics in order to reduce the inequalities of work performed among the nursing technicians of the same institution. In addition to individual strategies, some issues need to be reorganized focusing on preventing the sickness of these professionals, such as: increasing the number of professionals to avoid overloading activities, providing better working conditions such as physical structure and materials in sufficient quantities for the assistance and better scaling of critical patients so that there is no overload in only a few surgical clinics. KEY WORDS: Common Mental Disorder, Nursing Technician, Surgical, Worker Health, Work Organization.